2015
DOI: 10.1371/journal.ppat.1004622
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and Dynamics of Effector and Memory CD8 T Cell Responses in Human Tick-Borne Encephalitis Virus Infection

Abstract: Tick-borne encephalitis virus (TBEV) is transferred to humans by ticks. The virus causes tick-borne encephalitis (TBE) with symptoms such as meningitis and meningoencephalitis. About one third of the patients suffer from long-lasting sequelae after clearance of the infection. Studies of the immune response during TBEV-infection are essential to the understanding of host responses to TBEV-infection and for the development of therapeutics. Here, we studied in detail the primary CD8 T cell response to TBEV in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 59 publications
8
69
0
Order By: Relevance
“…DCs are also responsible for generating protective CD8 ϩ T-cell immunity using molecular signaling (104). The CD8 ϩ T-cell response was recently examined in depth in acute human TBEV infections, including temporal dynamics, specificity, and functional and phenotypical characteristics of the response (105). Another recent study suggested some major differences in the natural killer (NK) T-cell response against human TBEV infection compared to other human viral infections (106).…”
Section: Immunitymentioning
confidence: 99%
“…DCs are also responsible for generating protective CD8 ϩ T-cell immunity using molecular signaling (104). The CD8 ϩ T-cell response was recently examined in depth in acute human TBEV infections, including temporal dynamics, specificity, and functional and phenotypical characteristics of the response (105). Another recent study suggested some major differences in the natural killer (NK) T-cell response against human TBEV infection compared to other human viral infections (106).…”
Section: Immunitymentioning
confidence: 99%
“…1A, Supplemental Fig. 2A) (16). Significant CD8 + T cell responses were also observed against the HLA-B7-restricted epitopes B7-3 (RPVWKDARM), B7-4 (RVRFHSPAV), and B7-6 (LPLGHRLWL) (major epitopes) ( Fig.…”
Section: Identification Of Novel Hla-a2-and Hla-b7-restricted Tbev Epmentioning
confidence: 85%
“…Monitoring of Ag-specific CD8 + T cell populations is essential to dissect distinct characteristics in immune responses to a certain pathogen and to delineate the role of virus-specific CD8 + T cells during acute and persistent infections as well as long-term protection. We have previously demonstrated that CD8 + T cell responses in peripheral blood of TBE patients peak at around 7 d after hospitalization during the acute neuroinvasive phase of the disease (16). In that study, we identified one HLA-A2-restricted TBEV epitope and demonstrated that TBEV-specific CD8 + T cells display a distinctive phenotypic and functional profile, paired with a distinct transcription factor expression pattern during the peak of activation.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations